EFFORTS TO UNDERSTAND COMMUNITY LAW THROUGH UTILIZATION OF LEGAL CONSULTATION AND AID UNITS - Birkah Latif; Aidir Amin Daud; Padma D Liman; Ahmad Fikrul Ridha; Agung Syaputra (HERMENEUTIKA : Jurnal Ilmu Hukum, 2023)
Legal Counseling for Residents of Moncongloe Lappara Village, Moncongloe District, Maros Regency in Understanding Legal Issues Through Utilization of the Legal Consultation and Aid Unit at the Faculty of Law, Hasanuddin University conducted by the PPMU-PK-M Team of Hasanuddin University Research and Community Service Institute for partners (Village Heads of Moncongloe Lappara). A number of legal problems occurred in Moncongloe Lappara Village, Moncongloe District, Maros Regency, such as cases of buying and selling land belonging to other people, criminal acts of consumer protection, fraud, and the environment, so PPMU-PK-M activities can become a forum for the community and village officials in mapping problems and finding legal solutions by providing legal education and understanding for the community and village officials.